Optimization of in vitro fertilization with X-sorted spermatozoa in cattle - Fagali Franchi, Fernanda; Musmeci, Giulia; Alyfanti, Elena; Puelker, Raquel; Lodde, Valentina; Franciosi, Federica (Frontiers in Animal Science, 2026)
IntroductionDairy farming has a preferential demand for female calves to sustain milk production. Spermatozoa carrying the X chromosome, selected based on the higher content in DNA, allow to obtain almost exclusively female offspring. However, the separation procedures are stressful to the cells and induce mechanical and chemical modifications that negatively impact the survival, motility, and ultimately the fertilization potential. AIM: Considering that overall the X-sorted spermatozoa are characterized by compromised membrane integrity and premature capacitation, a series of experiments was conducted to test some optimizations of the in vitro fertilization (IVF) procedures to increase the embryo yield using commercially available X-sorted semen.MethodsThree series of experiments were conducted that led us to progressively refine the IVF procedure with X-sorted spermatozoa. First different protocols for semen processing were assessed for the yield in motile spermatozoa. Then the most promising were used in an IVF setting to investigate the fertilization ability. Finally the most performant protocol was used to investigate the effect of different IVF co-incubation times on the embryo yield.ResultsBy modifying some parameters of the discontinuous density gradient centrifugation such as the volume of the gradient, the proportion of PVP-coated colloidal silica solution, the centrifugation speed and the time of processing, along with the duration of the IVF culture, higher motility and fertilization and blastocyst rates were obtained (P<0.05).DiscussionOverall, while studies indicate that different bulls may require specific conditions for optimal fertilization and embryo yield, the present report shows that small adjustments to semen processing can significantly improve the efficiency of the in vitro embryo production with X-sorted semen.